P‐100: Approach on Two‐Step 3D Warping with Background Filling for Multi‐View Autostereoscopic Display. Issue 1 (May 2017) - Xiao, Fei; Xiong, Zhao-Long; Deng, Huan; Xing, Yan; Wang, Qiong-Hua
Abstract : We propose an approach on two‐step 3D warping with background filling for the multi‐view autostereoscopic display. The method can obtain high quality virtual view images, and the multi‐view autostereoscopic image is synthesized by using reference images and virtual view images. The experimental results show the effectiveness of the method for the autostereoscopic display.